Weakening patterns of intervocalic voiced plosives in Japanese - Li, Weiyu; Mizoguchi, Ai; Morimoto, Maho; Arai, Takayuki (The Journal of the Acoustical Society of America, 2023)
Japanese voiced plosives have been observed to exhibit weakened burst intensity, and in some instances, they may show a complete weakening with no observable burst. Maekawa (2010) investigated the weakening rate of voiced plosives in Japanese and its relationship with surrounding acoustic environments. His study revealed a notable tendency for consonant weakening, particularly at positions characterized by weak prosodic boundaries. However, despite referring to a general phenomenon of consonant weakening, there exist various pronunciation patterns. The articulatory gestures responsible for generating these diverse weakening patterns have not yet been thoroughly investigated. In this research, we conducted recording experiments involving native Japanese speakers, simultaneously capturing tongue movements using an ultrasound device. Our focus was directed towards the patterns of weakening observed in intervocalic Japanese voiced plosives and how to classify them. We identified three major patterns of plosives consonant weakening: (1) Voiced glide pattern, (2) Voiced frication pattern, and (3) Pattern with halted vocal fold vibration and weak aspiration. Variation was found in the frequency of occurrence of these patterns among alveolar, velar, and bilabial plosives. It is important to note that the rate of specific weakening patterns at different articulatory points varies among individuals. Additionally, for alveolar and velar sounds, tongue movement was analyzed using ultrasound imaging.